“For Generations, Farmers Have Preserved the Environment, Now You Are Endangering It”: Affective-Discursive Practices in European Farmers’ Reaction to Climate Policy (Czech Journal of International Relations, 2025)
The farming sector is one of the sectors most affected by climate change while simultaneously contributing to around 20% of global greenhouse emissions. To alleviate the pressures of agricultural production on nature and climate, the European Union (EU) established a new set of agri-environmental regulations positioning farmers as crucial actors in providing sustainable food and safeguarding the environment. However, farmers are increasingly contesting these regulations and mobilizing through EU-wide protests. Despite the obvious potency of the farmers’ actions, scholarly studies problematizing their manifestation in the context of climate governance are scarce. This paper addresses this gap by analyzing the 2023–2024 farmers’ protests in Slovenia to examine the interplay of affects and discourse in meaning-making among the farmers, which shows a mobilization driven by anger and fear as well as self-importance. The paper thus contributes to the knowledge on agrarian populism and farmers’ mobilizations in the European context, uncovering complexities and nuances of the articulated affective-discursive canon.
Keywords: farmers' protest; affects; affective-discursive practices; agri-environmental regulation